PERBANDINGAN STATUS FUNGSIONAL SAAT MASUK ANTARA PASIEN DEWASA DENGAN HIPERTENSI, DIABETES, STROKE, DAN TUBERKULOSIS - Anderson, Elisa; Manoppo, Arlien J (Fakultas Keperawatan, Universitas Klabat, 2026)
Hypertension, diabetes mellitus, stroke, and tuberculosis are the main chronic diseases in adults in Indonesia and have an impact on functional status decline, but functional comparisons between these diseases upon admission to the hospital are rarely studied. This study aims to compare the functional status upon admission of adult patients with these four diseases in a hospital in North Sulawesi using the Katz Index. The study design was cross-sectional with convenience sampling of 206 adult patients who met the inclusion criteria. Functional status was assessed using the Katz Index, analyzed descriptively and with the Kruskal-Wallis and Mann-Whitney tests. The highest mean functional scores were found in hypertension (3.89) and DM (3.66), followed by TB (3.06), and the lowest in stroke (2.31), with significant differences between groups (p = 0.001); further tests showed significant differences between stroke vs. hypertension/DM and between hypertension vs. TB. It was concluded that the type of disease was closely related to the level of independence in activities of daily living, with stroke being the most vulnerable group to disability. This study recommends the routine application of the Katz Index assessment upon admission and the development of disease-specific function-based nursing care protocols to maintain or improve patient independence. Hipertensi, diabetes melitus, stroke, dan tuberkulosis merupakan beban utama penyakit kronis pada dewasa di Indonesia dan berdampak pada penurunan status fungsional, namun perbandingan fungsional antar penyakit ini saat masuk rawat inap masih jarang dikaji. Penelitian ini bertujuan membandingkan status fungsional saat masuk pada pasien dewasa dengan keempat penyakit tersebut di sebuah rumah sakit di Sulawesi Utara menggunakan Katz Index. Desain penelitian adalah potong lintang dengan teknik convenience sampling terhadap 206 pasien dewasa yang memenuhi kriteria inklusi. Status fungsional dinilai menggunakan Katz Index, dianalisis secara deskriptif dan dengan uji Kruskal‑Wallis serta Mann‑Whitney. Rata‑rata skor fungsional tertinggi terdapat pada hipertensi (3,89) dan DM (3,66), diikuti TB (3,06), dan terendah pada stroke (2,31), dengan perbedaan bermakna antar kelompok (p=0,001); uji lanjut menunjukkan perbedaan signifikan antara stroke vs hipertensi atau DM dan antara hipertensi vs TB. Disimpulkan bahwa jenis penyakit berkaitan erat dengan tingkat kemandirian aktivitas sehari‑hari, dengan stroke sebagai kelompok paling rentan disabilitas. Rekomendasi studi ini adalah penerapan penilaian Katz Index secara rutin saat masuk dan pengembangan protokol asuhan keperawatan berbasis fungsi yang spesifik per penyakit untuk mempertahankan atau meningkatkan kemandirian pasien.